2017
DOI: 10.1155/2017/4182546
|View full text |Cite
|
Sign up to set email alerts
|

Study on Electrophysiological Signal Monitoring of Plant under Stress Based on Integrated Op-Amps and Patch Electrode

Abstract: Electrophysiological signal in plant is a weak electrical signal, which can fluctuate with the change of environment. An amplification detection system was designed for plant electrical signal acquisition by using integrated op-amps (CA3140, AD620, and INA118), patch electrode, data acquisition card (NI USB-6008), computer, and shielded box. Plant electrical signals were also studied under pressure and flooding stress. The amplification detection system can make nondestructive acquisition for Aquatic Scindapsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Studies have found patterns of electrical potentials in plants under water stress, in [96][97][98]15,55,22] was observed an increase in the electrical signal in non-irrigated fruit plants, which changes when starting irrigation, producing a negative signal slope until reaching stability under normal conditions of irrigation. The roots can feel the soil's drying and send signals to the leaves to coordinate the processes over a long distance, especially in large plants where water transport is slower [99] (Fig.…”
Section: Monitoring and Study Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found patterns of electrical potentials in plants under water stress, in [96][97][98]15,55,22] was observed an increase in the electrical signal in non-irrigated fruit plants, which changes when starting irrigation, producing a negative signal slope until reaching stability under normal conditions of irrigation. The roots can feel the soil's drying and send signals to the leaves to coordinate the processes over a long distance, especially in large plants where water transport is slower [99] (Fig.…”
Section: Monitoring and Study Systemsmentioning
confidence: 99%
“…Electrodes as: Ag/AgCl electrode [24][51], nonpolarizable reversible Ag/AgCl electrodes prepared from Teflon coated silver wire [52][53][54], graphite patch electrodes [55].…”
Section: Plant Extracellular Measurementmentioning
confidence: 99%